Lighting for televised live events : making your live production look great for the eye and the camera - Moody, James L.; Ravitz, Jeff (Routledge, Taylor & Francis Group, 2021)
"Lighting for live televised events unlocks the science, art, philosophies, and language of creating lighting for live entertainment and presentations that work for the television camera as well as for the live audience. The book explores how to retain the essence and excitement of a live production while assuring that the show looks its best on-camera for the millions of viewers that can only see it on their TV, computer, tablet, or mobile phone screen. Readers will learn how to adapt an existing stage show for the camera, as well as how to design live entertainment or events specifically for TV. Filled with real-life examples and illustrations, the book covers a wide range of topics, including : how exposure and color work for the camera ; how angle, visual balance, and composition can make people and backgrounds look their best, while preserving theatricality ; information on camera equipment, screens, and projectors, as well as the control room environments that are found on a professional shoot ; the unique challenges of lighting for the IMAG video screens used at festivals and concerts. Lighting for live televised events is aimed at lighting design students, as well as professional designers that are considering a career - or a career expansion - in television. It is an essential resource for any stage lighting designer whose show may be shot for a television special or a live webcast and who will be asked by their client to collaborate with the incoming video team"--